An evaluation of the effectiveness of immersive virtual reality training in non-specialized medical procedures for caregivers and students: a brief literature review - Clay, Casey J.; Budde, John R.; Hoang, Andrea Q.; Gushchyan, Armen (Frontiers in Virtual Reality, 2024)
As technological advancements continue to redefine the landscape of adult education and training, virtual reality (VR) has emerged as a potent tool for enhancing skill acquisition. This literature review synthesizes existing research on the utilization of immersive and discrete VR in training adults in the medical domain. The primary focus was on understanding the effectiveness, challenges, and potential applications of VR-based training programs. Specifically, we reviewed studies related to practical skills critical to safety that target a non-surgical, discrete medical procedure (e.g., diabetes care procedures, how to correctly set a G-tube, CPR, correct personal protection equipment [PPE] usage) using an immersive VR technology as a training modality. Further, the studies reviewed had to include a comparison of immersive VR training to that of a business-as-usual (BAU) method. We conducted a review of the six studies that met the criteria and coded variables related to what technology was used, targeted skills being trained, social validity, effectiveness of the intervention, and whether generalization occurred. Key themes explored in the literature include the role of immersive experiences in enhancing learning outcomes when comparing VR training to BAU and the adaptability of VR platforms to different skill sets. Special attention was given to identifying factors that contribute to the success or limitation of VR-based training initiatives, including individual differences, technology acceptance, and effectiveness.